1984
DOI: 10.1007/bf00848953
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium mobilization on stimulation of the muscarinic cholinergic receptor in chick limb bud cells

Abstract: Cell suspensions of chick limb buds (stage 23/24) were loaded with the fluorescent Ca chelator chlorotetracycline. Fluorescence was monitored in a spectrofluorometer. Stimulation with acetylcholine induced a fluorescence decrease, indicating intracellular Ca mobilization. The fluorescence decrease triggered by acetylcholine was inhibited by muscarinic but not by nicotinic antagonists, indicating that a muscarinic acetylcholine receptor is involved. The muscarinic receptor in the chick limb bud has a characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The poor efficacy of pilocarpine and bethanechol may reflect a partial agonist action as seen in sympathetic ganglia (Burgen & Spero, 1968;Brown et al, 1980), parasympathetic postganglionic neurones (Goyal & Rattan, 1978), embryonic chick limb bud cells (Schmidt et al, 1984), the phosphoinositide response in the brain (Fisher et al, 1983) and the inhibition of stimulated cyclic AMP formation in neuroblastoma cells (McKinney et al, 1985). These agonists are generally considered to show little or no activity at nicotinic receptors in ganglia (Caulfield & Stubley, 1982;Gilman et al, 1985) or skeletal muscle (Clague et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The poor efficacy of pilocarpine and bethanechol may reflect a partial agonist action as seen in sympathetic ganglia (Burgen & Spero, 1968;Brown et al, 1980), parasympathetic postganglionic neurones (Goyal & Rattan, 1978), embryonic chick limb bud cells (Schmidt et al, 1984), the phosphoinositide response in the brain (Fisher et al, 1983) and the inhibition of stimulated cyclic AMP formation in neuroblastoma cells (McKinney et al, 1985). These agonists are generally considered to show little or no activity at nicotinic receptors in ganglia (Caulfield & Stubley, 1982;Gilman et al, 1985) or skeletal muscle (Clague et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…After cell differentiation, this muscarinic system disappears. In chicken limb buds it was shown that stimulation of the muscarinic receptor causes alterations in cell shape and movement (Schmidt et al, 1984;Oettling et al, 1985). Since a rise in acetylcholinesterase activity is also described for differentiation of non-nerve cells in Tenebrio molitor (Lenoir-Rousseaux and Gautron, 1987) and in developing imaginal discs of D. melanogarter (Spindler-Barth and Milner, unpublished), this "cholinergic system" may also play a role in insect cell differentiation.…”
Section: Hormonally-induced Differentiationmentioning
confidence: 97%
“…The cholinesterase activity in non-neural cells indicated the involvement of a primitive cholinergic system, the components of which could be demonstrated biochemically in the embryo: cholinesterase activity was accompanied by expression of choline acetyltransferase (Reich and Drews 1983) and muscarinic receptors (Schmidt 1981). In cell suspensions, stimulation of the muscarinic receptor led to intracellular calcium mobilization (Schmidt et al 1984), which in turn could be used for the pharmacological characterization of the receptor itself (Oettling et al 1985).…”
Section: Introductionmentioning
confidence: 99%